Gamma-knife radiosurgery for jugular foramen schwannomas. A systematic review and meta-analysis - Timoleon Siempis; Spyridon Voulgaris; George A. Alexiou (World Neurosurgery: X)
Introduction: Jugular Foramen Schwannomas (JFS) have been traditionally treated with surgical resection with an associated significant post-operative morbidity. Stereotactic radiosurgery has been investigated as potentially minimally invasive alternative to microsurgery. The aim of this study was to provide a systematic review and meta-analysis of the available literature regarding the outcomes of cases of JFS treated with radiosurgery. Methods: A literature review until 28th of March 2023 was performed. All studies looking at the outcomes of radiosurgery for the treatment of JFS were included. Studies including non-vestibular schwannomas without clear distinction of the tumour type were excluded. Risk of bias was assessed using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) scale. Results: Eight (8) studies with a total of 375 patients met the inclusion and exclusion criteria and were included in the analysis. Pooled overall tumour control rate was 93.2 % (95 % CI 89.8–96.6) after a weighted mean follow-up of 54.07 months (95 % CI 46.8–61.3). Patient free survival was reported only in 4 studies and ranged from 87 % to 97 % and 76.9–93.8 % in 5 and 10 years respectively. The radiation induced cranial nerve deficits rates after GKRS were 3.6 % (95%CI 1.7, 5.5 %). Conclusion: According to our findings, radiosurgery for JFS has favourable clinical outcomes with a high rate of long-term tumour control and low complication rates.